Uncovering the surge: dengue fever on the rise - Wheaton, Noah; Wong, Christian; Gasmelseed, Huda; Zinabu, Samrawit; Sood, Aseem; Rajendran, Rithika; Shead, Madison; Sanders, Amaya; Norton, Tabitha; Michael, Miriam (Frontiers in Epidemiology, 2025)
IntroductionDengue fever, traditionally a tropical disease, has shown a notable increase in incidence within the United States over recent decades. This paper focuses on the increase in dengue fever cases in Maryland during increasing temperature and humidity and the expanding geographical range of Aedes mosquitoes, the primary vectors for dengue virus transmission.MethodsElectronic health data was used to identify patterns in dengue incidence from 2014 to 2024. Correlation analysis between temperature and dengue incidence and a review of humidity factors was conducted.ResultsResults indicate an increased incidence of dengue fever cases over the past decade. However, a reduction in dengue incidence was observed in 2019–2020, likely due to COVID-19-related travel restrictions.DiscussionAs global temperatures increase, the habitats suitable for Aedes mosquitoes have expanded, allowing for their proliferation in previously inhospitable regions. Additionally, higher temperatures can accelerate the life cycle and viral replication rates in these mosquitoes, further enhancing transmission potential. Humidity, another key environmental factor, influences the life expectancy of dengue mosquitoes. This research underscores the urgency of addressing climate change as a public health issue, emphasizing the need for integrated vector management strategies and public health preparedness to mitigate the growing threat of dengue in temperate regions. By understanding the interplay between global warming, humidity, and dengue transmission, we can better inform policy decisions and healthcare practices to curb the spread of this disease in Maryland and the United States.